Is the association between poor job control and common mental disorder explained by general perceptions of control? Findings from an Australian longitudinal cohort - Lay San Too; Liana Leach; Peter Butterworth (Nordic Association of Occupational Safety and Health (NOROSH), 2020)
OBJECTIVES: This study sought to examine the influence of general perceptions of control on the association between job control and mental health. METHODS: We used four waves of data from a cohort of mid-aged adults from the Personality and Total Health (PATH) Through Life Study (baseline N=2106). Key measures included job control and likelihood of experiencing a common mental disorder (anxiety and/or depression). The data were analyzed using longitudinal random-intercept regression models, controlling for a range of potential confounders including general perceptions of control (ie, not isolated to the work context) via a measure of mastery. The analyses isolated the effect of within-person changes in job control on mental health (apart from between-person differences). RESULTS: The results show that the effect of job control remained significant after adjusting for general perceptions of control and other confounders. The within-person effect in the model demonstrated that, when workers had low job control, they were twice as likely to experience a common mental disorder [odds ratio (OR) 2.04, 95% confidence interval (CI) 1.53‒2.73]. CONCLUSIONS: Individuals' general perceptions of control in life does not account for the association between low job control and poor mental health. The findings add a new layer of evidence to the literature demonstrating that lack of autonomy at work is an independent predictor of employees' mental health. Increasing employee control should be integrated into workplace strategies to promote mental health.